Fish and Meat Are Often Withheld From the Diets of Infants 6 to 12 Months in Fish-Farming Households in Rural Bangladesh. Issue 3 (September 2017) - Thorne-Lyman, Andrew L.; Valpiani, Natalie; Akter, Rumana; Baten, Md Abdul; Genschick, Sven; Karim, Manjurul; Thilsted, Shakuntala H.
Background: Fish is a widely available animal-source food in Bangladesh and a rich source of nutrients, yet little is known about practices related to incorporating fish into the diets of infants and young children. Objective: Use dietary diversity data to explore consumption patterns of fish and high-quality food items within the household and examine factors associated with delayed introduction of fish to infants and young children. Methods: Cross-sectional survey of 496 households with children <36 months participating in the Aquaculture for Income and Nutrition project in Bangladesh. Data collected included household characteristics, women's dietary diversity score, and minimum dietary diversity score along with data on Infant and Young Child Feeding practices. Results: Most children (63.4%) met the threshold for minimum dietary diversity. Despite having received extensive nutrition education related to including fish in complementary foods, only half of the caretakers introduced fish at 6 months and the mean age of introduction of small fish was 8.7 months. Meat and fish were not common in infant diets but increased with child age. Concerns about bones were a major barrier to incorporating fish into infant diets. Conclusion: Given its nutrient profile and widespread availability in certain contexts, fish could be an underutilized opportunity to improve nutrition and health outcomes of infants and young children. Further research, including utilizing food processing technologies, is needed to develop appropriate responses to overcome these barriers.